Potential for using sepiolite as dispersing agent in phenolic resin crosslinked natural rubber/silica composites - Nabil Hayeemasae; Sitisaiyidah Saiwari; Siriwat Soontaranon; Mohamad Irfan Fathurrohman; Abdulhakim Masa (eXPRESS Polymer Letters)
Natural rubber (NR) composites filled with silica and crosslinked with phenolic resin were prepared in this study. The influence of a small sepiolite addition (1–5 part(s) per hundred parts of rubber, phr) on the properties of NR composites was studied. It was found that sepiolite reduced silica aggregate size, allowing improved dispersion in the NR matrix. Sepiolite facilitates silica dispersion by locating at the silica surfaces and acting as a barrier that prevents agglomeration of silica filler. The swelling resistance, crosslink density, tensile strength, and strain-induced crystallization were all strengthened by incorporating sepiolite because of the improved silica dispersion. The greatest tensile strength was achieved at a 2 phr sepiolite addition level. The improvement was about 18% over the reference composite due to the greatest filler-rubber interactions and the finest filler dispersion. The results clearly indicate that sepiolite clay can be applied as a dispersing agent in silica-containing rubber composites.